Socio-Educational Challenges for the Inclusion of Children with Cochlear Implants: The Role of Families - Pablo Cortés-González; Deseada Ruiz-Ariza; Moisés Mañas-Olmo; Carolina Alix-González (Education Sciences)
The article examines the socio-educational barriers and facilitators faced by families of children with cochlear implants (CI) in Andalucía (a region in southern Spain). Through a qualitative approach based on surveys and interviews, three main categories of limitations are identified: access to and quality of services, parental stress related to caregiving and communication, and socioeconomic and individual factors. Among the facilitators, financial support, family-professional collaboration, and inclusive practices in educational settings are highlighted. The findings underscore challenges such as the lack of coordination between medical and educational services, the need for teacher training, and the emotional and financial impact on families. Conversely, effective strategies such as family support networks, specialized hospital coordinators, and inclusive educational practices are emphasized. The study concludes that improving access to comprehensive services and fostering collaboration between educational and healthcare agents is essential to promote inclusive education and the well-being of families and children with CI. This work advocates for a critical and participatory perspective in the development of inclusive policies.